Poly (ADP-Ribose) Polymerase Inhibitors: Recent Advances and Future Development - Scott, Clare L. (J Clin Oncol, 2015)
Poly (ADP-ribose) polymerase (PARP) inhibitors have shown promising activity in epithelial ovarian cancers, especially relapsed platinum-sensitive high-grade serous disease. Consistent with preclinical studies, ovarian cancers and a number of other solid tumor types occurring in patients with deleterious germline mutations in BRCA1 or BRCA2 seem to be particularly sensitive. However, it is also becoming clear that germline BRCA1/2 mutations are neither necessary nor sufficient for patients to derive benefit from PARP inhibitors. We provide an update on PARP inhibitor clinical development, describe recent advances in our understanding of PARP inhibitor mechanism of action, and discuss current issues in the development of these agents.